Effect of Centella asiatica Extract on Locomotor Activity and Hsp60 Expression in Zebrafish models of Parkinsons - Rodhiyan Rakhmatiar; Mulyohadi Ali; M. Dalhar (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Brawijaya, 2020)
Parkinson's disease characterized by a decrease in motor activity is a progressive neurodegenerative disorder caused by the degeneration of dopaminergic neurons. Centella asiatica is suspected of having a neuroprotectant effect and is not yet known how Centella asiatica role in the prevention of Parkinson's disease. The study was conducted to prove the effect of Centella asiatica extract on the expression of Hsp60 and locomotor activity zebrafish models of Parkinson's with rotenone exposure. The study was conducted using 25 zebrafish divided into various groups. Centella asiatica extract and rotenone exposure have given for 28 days, observed locomotor activity on days 0, 7, 14, 21 and 28. The expression of Hsp60 measured using immunohistochemical techniques. There is a significant difference between locomotor activity at various doses of Centella asiatica (p<0.05) with a very strong correlation (r=0.929; p<0.01) where the higher doses of Centella asiatica, the higher locomotor activity. Found a significant difference between the reduced expression of Hsp60 to various Centella asiatica dose group (p<0.05) but no correlation between the expression of Hsp60 with Centella asiatica dose groups and locomotor activity. Centella asiatica extract is able to increase locomotor activity and decrease the expression of Hsp60 in zebrafish models of Parkinson's.